MEMETAKAN JASA PENDIDIKAN JURUSAN PAI FITK IAIN SURAKARTA MELALUI BUSINESS MODEL CANVAS - Abu Choir (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2014)
This study tries to explore the srategy of mapping the service of Islamic Education Department of Tarbiyah and Teacher Training Faculty of IAIN Surakarta by using business canvas model. The aim of this study is to describe and find business canvas model to map the service of Islamic education department. The result showed that the service mapping of Islamic education department can be used as a media for quality assessment of Islamic education department. Based on the scope of business canvas model which has been designed, analyzed, and finalized, it was found the service mapping of students, lecturers, staffs, FITK leaders, and Islamic education teachers. Keywords: Service; Islamic Education; Business Canvas Model